The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/w14223717
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Photo-Fenton Activity Using Magnetic Cu0.5Mn0.5Fe2O4 Nanoparticles as a Recoverable Catalyst for Degrading Organic Contaminants

Abstract: Interest in using various nanoparticle catalysts to activate H2O2 with light for organic contaminant and wastewater treatment is steadily increasing. We successfully synthesized magnetically recoverable Cu0.5Mn0.5Fe2O4 nanoparticles using a simple co-precipitation method followed by melamine-assisted calcination. Material characterization revealed that melamine acted as a coordinating agent during the calcination process that promoted a ferrite structure. Copper (Cu)-substitution effectively decreased material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 58 publications
2
9
0
Order By: Relevance
“… 26 Both XRD and FTIR results confirmed our successfully synthesized catalyst using coprecipitation followed by the melamine-assisted calcination method. Angkaew et al 27 reported that g-C 3 N 4 served as a coordinating agent by forming a metal–melamine complex and/or conjugating with a metal oxide. Under the calcining temperature (550 °C), this complex can further decompose into a spinel ferrite structure and volatile gases (i.e., CO X , NO X , and NH 3 ), successfully preventing α-Fe 2 O 3 formation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“… 26 Both XRD and FTIR results confirmed our successfully synthesized catalyst using coprecipitation followed by the melamine-assisted calcination method. Angkaew et al 27 reported that g-C 3 N 4 served as a coordinating agent by forming a metal–melamine complex and/or conjugating with a metal oxide. Under the calcining temperature (550 °C), this complex can further decompose into a spinel ferrite structure and volatile gases (i.e., CO X , NO X , and NH 3 ), successfully preventing α-Fe 2 O 3 formation.…”
Section: Resultsmentioning
confidence: 99%
“…If it was there, it might have been a rapid reaction, and the Fe 3+ was insufficient to react with a large amount of O 2 •– , thereby O 2 formation was only minimal. Moreover, Angkaew et al 27 showed that the ferrites also have photocatalytic performance and were able to produce • OH under light irradiation [ eq 8 ]. Because of the O 2 •– abundance, we ruled out that, once released, the • OH would simultaneously react and provide more 1 O 2 into the system, concordant with our scavenging experiment that rooted for 1 O 2 production.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is due to the various valences in the nanocomposites, including Mn 4+ , Mn 3+ , Mn 2+ , Fe 3+ , and Fe 2+ , which can trigger the synergistic action between the Mn and Fe redox cycles [10,11]. Furthermore, doping manganese ferrite structures with another transition metal (e.g., Cu) can produce ternary transition metal oxides (e.g., Cu 0.5 Mn 0.5 Fe 2 O 4 ), which have a greater surface area than iron-based transition metal catalysts [12,13]. This is beneficial to photo-Fenton-like AOP treatments by providing larger active sites, an excellent oxygen exchangeability, and an outstanding capability for electron transfer through the Cu 2+ /Cu 1+ redox cycle.…”
Section: Introductionmentioning
confidence: 99%